Translation and validation of a Chinese version of the Warwick–Edinburgh Mental Well‐being Scale with undergraduate nursing trainees. Issue 9 (November 2016) - Dong, A.; Chen, X.; Zhu, L.; Shi, L.; Cai, Y.; Shi, B.; Shao, L.; Guo, W.
Accessible summary: What is known on the subject?: Warwick–Edinburgh Mental Well‐being Scale (WEMWBS) which is a measurement of mental health and well‐being, was translated into Chinese to assess the reliability and validity in a sample of undergraduate nursing trainees in Wenzhou. What this paper adds to existing knowledge?: Currently, there is no a reliable assessment tool to systematically evaluate mental well‐being in mainland China. Therefore, we undertook the translation and cultural adaptation of the WEMWBS and tested the scale's reliability and validity. The reliability and validity of the Chinese version of the Short Warwick–Edinburgh Mental Well‐being Scale have been demonstrated in Hong Kong, but the WEMWBS has not been validated in mainland China in either clinical or non‐clinical settings. What are the implications for practice?: It might provide a reliable quantitative tool to evaluate mental well‐being in non‐clinical settings, which has important implications for mental health nursing. In future, it might be a reliable quantitative tool for evaluating mental well‐being in other population such as hospitalized patients to improve their life quality. Abstract: Introduction: There is growing interest worldwide in the evaluation of positive mental health and wellbeing. Aim: This study was to translate the Warwick–Edinburgh Mental Well‐being Scale (WEMWBS) into Chinese and assess the reliability and validity of this scale in a sample of undergraduate nursing trainees. Methods: A forward and backward translation protocol was used to translate the scale into Chinese. The psychometric properties of the C‐WEMWBS, such as internal consistency reliability, test–retest reliability and factorial validity, were analysed. Results: All 14 items of the initial C‐WEMWBS were rated as conceptually equivalent to those of the original version. Confirmatory factor analysis indicated the emergence of a single factor. The psychometric properties of the C‐WEMWBS were satisfactory, with an internal consistency reliability of .94 and a test–retest reliability of .83. The item–total correlations ranged from .66 to .83. There was a moderate relationship ( r = .52) between the C‐WEMWBS and the WHO‐5. Implications for practice: This was the first Chinese version of the WEMWBS to be developed and psychometrically assessed with a sample of undergraduate nursing trainees. It provides a reliable quantitative tool to evaluate mental well‐being in non‐clinical settings, which has important implications for mental health nursing.